PENGARUH BELANJA PEMERINTAH DAN INVESTASI PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI (Studi Kasus pada Kabupaten Sekadau, Melawi dan Sintang) - B61112016, RIO ROSSANDI NURIAN (Jurnal Ekonomi Daerah (JEDA), 2016)
This research has an intention to find out whether the allocation of government spending and government investment terehadap affect economic growth in Sekadau, Melawi and Sintang. The purpose of this study was to examine and analyze the effect of government spending and government investment to economic growth in Sekadau, Melawi and Sintang. This research used explanatory, with data from 2007 up to 2012, this study intends to examine and explain the relationship between independent variables and the dependent variable. As for the variables in this study are: government spending, government investment and economic growth. The results showed a significant effect that the value of F at 8.553 with a probability value of 0.003, meaning that the variable government spending and government investment simultaneously influence / significantly to economic growth, with a coefficient of determination (R2) of 0.533, meaning that the influence exerted on the two variables amounted to 53.3% while the remaining 46.7% is influenced by other variables.